Some Human Dimensions of Understanding Flood Risk Management - Edmund C. Penning-Rowsell (Hydrology)
Flood risk management involves managing the consequences of flooding as well at its hazard characteristics. This means attending to the human effects of floods and flood risk reduction. These effects are many and varied and are often poorly understood by those who make the relevant decisions. This short piece addresses this issue and calls for a greater awareness of what measures those at risk are motivated likely to undertake to reduce the risks that they personally face.